Succinate aggravates intestinal injury in mice with necrotizing enterocolitis - Yan, Xiao-Lin; Liu, Xiao-Chen; Zhang, Yu-Ni; Du, Ting-Ting; Ai, Qing; Gao, Xiong; Yang, Jing-Li; Bao, Lei; Li, Lu-Quan (Frontiers in Cellular and Infection Microbiology, 2022)
Background Necrotizing enterocolitis (NEC) is the most prevalent gastrointestinal disorder that predominantly threatens preterm newborns. Succinate is an emerging metabolic signaling molecule that was recently studied in relation to the regulation of intestinal immunity and homeostasis. We aimed to investigate the relationship between NEC and gut luminal succinate and preliminarily explored the effect of succinate on NEC pathogenesis. Methods Fecal samples from human neonates and mouse pups were analyzed by HPLC – MS/MS and 16S rRNA gene sequencing. C57BL/6 mice were randomly divided into four groups: control, NEC, Lsuc, and Hsuc. The mortality, weight gain, and intestinal pathological changes in four mouse groups were observed. Inflammatory cytokines and markers of macrophages were identified by quantitative real-time PCR. Succinate receptor 1 (SUCNR1) localization was visualized by immunohistochemistry. The protein levels of SUCNR1 and hypoxia-inducible factor 1a (HIF-1a) were quantified by western blotting. Results The levels of succinate in feces from NEC patients were higher than those in feces from non-NEC patients (P <0.05). In the murine models, succinate levels in intestinal content samples were also higher in the NEC group than in the control group (P <0.05). The change in succinate level was closely related to intestinal flora composition. In samples from human neonates, relative to the control group, the NEC group showed a higher abundance of Enterobacteriaceae and a lower abundance of Lactobacillaceae and Lactobacillus (P <0.05). In the murine models, relative to the control group, increased abundance was observed for Clostridiaceae, Enterococcaceae, Clostridium_sensu_stricto_1, and Enterococcus, whereas decreased abundance was observed for Lactobacillaceae and Lactobacillus (P <0.05). Increased succinate levels prevented mice from gaining weight, damaged their intestines, and increased their mortality; upregulated the gene expression of interleukin-1β (IL-1β), IL-6, IL-18 and tumor necrosis factor (TNF); and downregulated the gene expression of IL-10 and transforming growth factor (TGF)-β. Exogenous succinic acid increased inducible nitric oxide synthase (iNOS) gene expression but decreased Arginase-1 (Arg1) gene expression; and increased the protein expression of SUCNR1 and HIF-1a. Conclusion Succinate plays an important role in the development of necrotizing enterocolitis severity, and the activation of the HIF-1a signaling pathway may lead to disease progression.